Barriers to sexual activity: counselling spinal cord injured women in Malaysia - Julia, P.E.; Othman, A.S. (Stockton Press, 2011)
Study design:This study is a cross-sectional, face-to-face interview.Objectives:To examine the sexual activity in a sample of Malaysian women with traumatic spinal cord injuries (SCIs), identify the physical and psychological barriers to it, and explore their experiences with sexual counseling and rehabilitation.Setting:This study was conducted at the Spinal Rehabilitation Unit of a teaching hospital.Methods:All women who attended scheduled check-ups, over 1 year, and who met the inclusion criteria (age above 18 years, spinal injury of traumatic aetiology, living in the community and having completed the rehabilitation) were consecutively included in a face-to-face interview using a self-constructed questionnaire. Sociodemographic and disability-related variables, barriers to sexual activity/satisfaction and experiences of sexual rehabilitation services were obtained.Results:During the study period, 33/36 subjects were recruited. Although 67% indicated interest in sexual activity, only 24% was sexually active. The frequency of sexual activity declined after the injury, from 4.6 times per month to 1.5 times per month. Feeling unattractive, unable to satisfy the partner and less confident about sexual ability were top three psychological barriers to sexual activity, and the top three physical barriers were impaired genital sensation, positioning and vaginal lubrication. In all, 50% received some sexual information during rehabilitation. Rehabilitation professionals were expected to initiate sexual counseling by 62.5% of subjects.Conclusion:The effect of SCIs on sexual function is tremendous. Sexual counseling services must be improved and take into account the impact of psychological factors.